Make your own party : twenty blueprints to MYO party! - Lewton, Kelli (Scribe Publishing Company, 2022)
"With party themes like 'Unicorns Trending,' 'Boho Beach,' 'Modern Pumpkin' and 'Party Bling,' the suggestions in this guide are guaranteed to take your parties to the next level. Each chapter offers a party blueprint with tips from event designer Kevin Miller, a full menu and recipes. Use the plan in its entirety or take what inspires you"--Page 4 of cover.